Ultras : the passion and performance of contemporary football fandom - Doidge, Mark; Kossakowski, Radosław; Mintert, Svenja (Manchester University Press, 2020)
Ultras have become the most dominant style of football fandom in the world having spread from Southern Europe across North Africa to Northern and Eastern Europe, SE Asia and North America. This book argues that ultras are an important site of enquiry into understanding contemporary society. They are a passionate, politically engaged collective that base their identity around a form of consumption (football) that links to modern notions of identity like masculinity and nationalism. 0'Ultras: the Passion and Performance of Contemporary Football Fandom' seeks to make a clear theoretical shift in studies of football fandom. Focussing on the common form of expression through the performance of choreographies, chants and sustained support throughout the match, this book shows how members build an emotional attachment to their club that valorises the colours and symbols of that team, whilst mobilising members against opponents.